A highly sensitive photothermal immunochromatographic sensor for detection of aflatoxin B1 based on Cu2-xSe-Au nanoparticles. (1st February 2023) - Wang, Qing; Li, Shijie; Zhang, Yu; Wang, Shouren; Guo, Jianping; Wang, Junping
Highlights: Cu2-x Se-Au with 60.78% photothermal conversion efficiency was synthesized. A new photothermal immunosensing probe was prepared. IC15 of photothermal immunochromatographic sensor for aflatoxin B1was 0.00842 μg/L. The detection ranging to analysize grain sample is from 0.16 to 160μg/kg. Abstract: In the study, Cu2-x Se-Au nanoparticles (CSA) with a photothermal conversion efficiency of 60.78 % at 808 nm were applied to the construction of thermal analysis immunochromatographic test strips for the highly sensitive quantitative detection of aflatoxin B1 (AFB1 ) in grain. The CSA was coupled with the AFB1 antibody to form a photothermal sensor probe by physical adsorption. The constructed immunosensor exhibited high sensitivity and a wide linear range from 0.01 to 10 μg/L in PBS. The detection limits of 0.00842 μg/L based on the thermal analysis was significantly improved by 11.88-fold compared with colorimetric results. No cross-reaction with the other mycotoxins was found except for aflatoxin B2, aflatoxin M1, aflatoxin G1 and aflatoxin G2 . Applied to analysize grain sample, the method achieved the detection of AFB1 ranging from 0.16 to 160 μg/kg.